Bibliometric Analysis of Sport Psychology Imagery Exercise in Scopus Indexed Scientific Articles 2010 – 2024 - Larasati, Sanggam; Sunadi, Didi; Hidayat, Yusuf; Kusnaedi; Ningrum, Desy Tya Maya (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2025)
This study aims to analyze related to Sports Psychology with Imagery exercises in Scopus-indexed Scientific articles using bibliometric analysis methods. From a total sampling of 1886 scientific articles from the publication years 2010–2024, selected from 208 scientific articles, collected from the Scopus page, with a data collection period from May to June 2024. Sampling was collected in Comma Separated Value (CSV) format, and VOSviewer was used to perform the bibliometric analysis method. From 208 scientific articles, 30 keywords that met the criteria for a minimum appearance of five times were collected and produced six mapping clusters. The mapping results show that imagery exercises are a research topic that is quite often used in research on Scopus-indexed scientific articles. The results of the analysis show that there has been development in research on imagery exercises in Scopus-indexed scientific articles.